"Booster" or "blocker"? A study on the effect of cultural diversity on foreign direct investment. Issue 1 (31st December 2022) - Feng, Wei; Yuan, Hang; Yang, Shuang
Abstract: In this paper, we investigate the characteristics and mechanisms of cultural diversity that affect foreign direct investment (FDI) using the panel data on provinces in China from 1999 to 2019 and find that, in general, cultural diversity inhibits FDI absorption. However, this kind of adverse effect has a nonlinear threshold characteristic. That is, when the population density reaches a certain level or urbanization is controlled within a certain range, the increase in cultural diversity can weaken the inhibitory effect on FDI. Additionally, by exploring the mechanisms of cultural diversity affecting FDI, we further find that cultural diversity inhibits FDI mainly through the channels of inhibiting population density and urbanization. The conclusions of this paper not only enrich the theoretical research on FDI location from the perspective of cultural diversity but also shed light on how to better attract FDI to China and other countries, such as resolving cultural conflicts and constructing an inclusive investment environment.